Strategic Foresight analysis of droughts in southern Africa and implications for food security - Gbegbelegbe, Sika; Chikoye, David; Alene, Arega; Kyei-Boahen, Stephen; Chigeza, Godfree (Frontiers in Sustainable Food Systems, 2024)
Droughts are projected to last longer and become more intense in southern Africa. This study contributes to the current literature by using bio-economic modeling to simulate the impact of future droughts on food security in southern Africa and identifying plausible pathways for enhancing regional food security under drought. Food production and food security in southern Africa were projected under drought using an adjusted version of a multi-market and multi-commodity global model, the International Model for the Policy Analysis of Agricultural Commodities and Trade (IMPACT), version 3.2. The results suggest that with moderate economic growth and no drought, southern Africa would not become wealthy enough to mitigate food insecurity by 2040. In this context, recurrent droughts would worsen food security by severely affecting the production of maize, the key staple food in the region. With consecutive two-year regional droughts, most countries would experience an increase of at least 10% in the number of people at risk of hunger within a single year. The results showed the importance of countries in southern Africa to reduce their dependence on maize as a staple food. Indeed, in countries where maize provides at least 20% of daily caloric intake, measures should be taken to diversify diets through promoting the production and consumption of drought-tolerant crops such as cowpea and cassava.